Localized field‐aligned currents in the polar cap associated with airglow patches. Issue 10 (11th October 2016) - Zou, Ying; Nishimura, Yukitoshi; Burchill, Johnathan K.; Knudsen, David J.; Lyons, Larry R.; Shiokawa, Kazuo; Buchert, Stephan; Chen, Steve; Nicolls, Michael J.; Ruohoniemi, J. Michael; McWilliams, Kathryn A.; Nishitani, Nozomu
Abstract: Airglow patches have been recently associated with channels of enhanced antisunward ionospheric flows propagating across the polar cap from the dayside to nightside auroral ovals. However, how these flows maintain their localized nature without diffusing away remains unsolved. We examine whether patches and collocated flows are associated with localized field‐aligned currents (FACs) in the polar cap by using coordinated observations of the Swarm spacecraft, a polar cap all‐sky imager, and Super Dual Auroral Radar Network (SuperDARN) radars. We commonly (66% of cases) identify substantial FAC enhancements around patches, particularly near the patches' leading edge and center, in contrast to what is seen in the otherwise quiet polar cap. These FACs have densities of 0.1–0.2 μA/m −2 and have a distribution of width peaking at 75 km. They can be approximated as infinite current sheets that are orientated roughly parallel to patches. They usually exhibit a Region 1 sense, i.e., a downward FAC lying eastward of an upward FAC. With the addition of Resolute Bay Incoherent Scatter radar data, we find that the FACs can close through Pedersen currents in the ionosphere, consistent with the locally enhanced dawn‐dusk electric field across the patch. Our results suggest that ionospheric polar cap flow channels are imposed by structures in the magnetospheric lobe via FACs, and thus manifest mesoscale magnetosphere‐ionosphere coupling embedded in large‐scale convection. Key Points: Localized large polar cap FACs (0.1–0.2 μA/m −2 ) are commonly observed around airglow patches collocated with fast flow channels The FAC sheets have a distribution of width peaking at 75 km and are orientated roughly parallel to patches The FACs usually exhibit a Region 1 sense and can close through Pedersen currents in the ionosphere through enhanced electric field